Formulation, consumer acceptability and commercial stability of pickled canned trout (Oncorhynchus mykiss) - Ortega-Barriga, Rosario Edely; Vilca-Huarilloclla, Estefani; Blanco-Espezua, María del Pilar; Araníbar-Béjar, Heidi Karol; Araníbar-Araníbar, Marcelino Jorge (Frontiers in Sustainable Food Systems, 2025)
Canning and acidification are preservation methods for perishable foods such as hydrobiological foods. The goal of this study was to determine the optimal pickled formulation of canned rainbow trout (Oncorhynchus mykiss) for overall acceptability by people and for the stability of the canned product while in storage. First phase, seven canned recipes with different proportions of trout filet (20 to 50%), vegetables (carrot, cauliflower, onion, green beans and peas) and covering liquid (vinegar, vegetable oil, common salt, cumin and pepper) for a total of 225 g were studied. Preservation with acetic acid (pH = 3.5 ± 0.05) and sterilization at 125 °C for 7 min were both used to stabilize the preserves. Recipe three of canned trout (35% trout filet; 35% vegetables; and 22% covering liquid and 8% free space) had the highest value from the sensory analysis by twelve trained panelists with 26.3 ± 1.63 points out of a total of 30 points. Recipe seven was the least accepted with 21.0 ± 1.41 (p < 0.001). In the second phase, in addition to sensory analysis, the critical quality and stability parameters were pH, histamine content and absence of microorganisms at 180 and 700 days of storage. Formula 3, was named S-Trubeche and was accepted by both women (88) and men (115) consumers (24.8 ± 1.85 vs. 24.7 ± 1.68; p < 0.495, respectively). Regarding the commercial stability of the canned product, a pH of 3.9 ± 0.17 was obtained after processing, increasing to 4.8 ± 0.12 at 180 days and 4.9 ± 0.15 at 700 days (p < 0.001). In general, the histamine content was less than 60 ppm and no mesophilic or thermophilic microorganisms were detected (commercial sterility, 0/9). According to the sensory analysis, quality parameters and stability over prolonged storage, we conclude that the best canned trout is recipe three with an equal proportion of trout filet and vegetables (35%) and with 22% of covering liquid.